Production Cost Analysis as a Control Tool at PT Perkebunan Nusantara IV Medan - Afifah Syahril; Renny Maisyarah (Journal of Management and Business Analytics, 2025)
This paper aims to analyze production costs as a tool for cost control at PT Perkebunan Nusantara IV Medan. Effective cost control is essential to ensure the efficiency and profitability of the company, par-ticularly in the plantation sector, where production costs significantly affect overall financial performance. The research method used is a descriptive analysis with a quantitative approach, focusing on data related to material costs, labor costs, and factory overhead costs. The results indicate that the company's production costs have not been optimally controlled, especially in the areas of indirect labor and maintenance expenses. Variance analysis between the standard costs and actual costs revealed significant deviations, which suggest inefficiencies in the production process. The study concludes that accurate and continuous analysis of pro-duction costs is a critical component for enhancing cost efficiency. It also recommends that management improve planning and cost monitoring mechanisms to support better decision-making and operational per-formance.